FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN FARMASI TAHUN 2017-2021: Cyntia Carolina, Nurapni Jami Putri - CAROLINA, CYNTIA; JamiPutri, Nurapni (LPPM STIA Nusantara Sakti, 2024)
The analysis tool used in this study was multiple linear regression analysis which was logged with the help of statistical software version 20. The source of the data came from IDX financial report data on the IDX website (www.idx.co.id). Data collection techniques were carried out using library research techniques. Based on the results of the study, it shows that: Information asymmetry has no significant effect on earnings management partially in this study, seen from the value , - tcount < -ttable or -0.209<2.201, or sig value> 0.05 (0.845>0, 05). Audit Quality There is no significant effect on Earnings Management partially in this study, seen from the tcount < ttable or 0.048 <2.201, or the sig value > 0.05 (0.964> 0.05). Ownership Structure There is a significant influence on Earnings Management partially in this study, seen in the value, tcount>ttable or 2.469>2.201, or sig value> 0.05 (0.069>0.05). The magnitude of the influence between information asymmetry, audit quality and ownership structure on earnings management is 34.1% (100% - 65.9%).